Centre Commissioned External Review (CCER) of pastoral systems - Little, P.D.; Dube, Sikhalazo (International Livestock Research Institute, 2011)
This report reviews key issues in pastoral systems research in tropical areas of sub-Saharan Africa and South Asia with the goal of identifying a ten-year research strategy for pastoral systems research for ILRI. It summarizes current work (ILRI and non-ILRI) on topics related to pastoral systems and identifies a focused set of recommendations for ILRI where the institute has a comparative advantage relative to the numerous other organizations conducting research on pastoralism; a proven or potential track record;‘ important set of productive partnerships (current or planned); and/or the existing or potential capacity to contribute to important pastoral systems research and policy in the future.